Long-term impact of HPV vaccination and COVID-19 pandemic on oropharyngeal cancer incidence and burden among men in the USA: A modeling study - Haluk Damgacioglu; Kalyani Sonawane; Jagpreet Chhatwal; David R. Lairson; Gary M. Clifford; Anna R. Giuliano; Ashish A. Deshmukh (Elsevier, 2022)
Summary: Background: Oropharyngeal cancer (OPC) incidence is rising rapidly among men in the United States of America (USA). We aimed to project the impact of maintaining the current HPV vaccination uptake and achieving 80% national (Healthy People) goal on OPC incidence and burden. Methods: We developed an open-cohort micro-simulation model of OPC natural history among contemporary and future birth cohorts of men, accounting for sexual behaviors, population growth, aging, and herd immunity. We used data from nationally representative databases, cancer registries from all 50 states, large clinical trials, and literature. We evaluated the status quo scenario (the current HPV vaccination uptake remained stable) and alternative scenarios of improvements in uptake rates in adolescents (aged 9-17 years) and young adults (aged 18-26 years) by 2025 to achieve and maintain the 80% goal. The primary outcome was to project OPC incidence and burden from 2009 to 2100. We also assessed the impact of disruption in HPV vaccine uptake during the COVID-19 pandemic. Findings: OPC incidence is projected to rise until the mid-2030s, reaching the age-standardized incidence rate of 9·8 (95% uncertainty interval [UI] 9·5-10·1) per 100 000 men, with the peak annual burden of 23 850 (UI, 23 200-24 500) cases. Under the status quo scenario, HPV vaccination could prevent 124 000 (UI, 117 000-131 000) by 2060, 400 000 (UI, 384 000-416 000) by 2080, and 792 000 (UI, 763 000-821 000) by 2100 OPC cases among men. Achievement and maintenance of 80% coverage among adolescent girls only, adolescent girls and boys, and adolescents plus young adults could prevent an additional number of 100 000 (UI, 95 000-105 000), 118 000 (UI, 113 000-123 000), and 142 000 (UI, 136 000-148 000) male OPC cases by 2100. Delayed recovery of the HPV vaccine uptake during the COVID-19 pandemic could lead to 600 (UI, 580-620) to 6200 (UI, 5940-6460) additional male OPC cases by 2100, conditional on the decline in the extent of the national HPV vaccination coverage and potential delay in rebounding. Interpretation: Oropharyngeal cancer burden is projected to rise among men in the USA. Nationwide efforts to achieve the HPV vaccination goal of 80% coverage should be a public health priority. Rapid recovery of the declined HPV vaccination uptake during the COVID-19 pandemic is also crucial to prevent future excess OPC burden. Funding: National Cancer Institute and National Institute on Minority Health and Health Disparities of the USA.